A 2-year follow-up of isolated Medial Patellofemoral Ligament Reconstruction by using soft suture anchor and adjustable cortical fixation system() - Mochizuki, Yuta (J Orthop, 2019)
PURPOSE: Numerous surgical techniques and fixation methods have been described in medial patellofemoral ligament (MPFL) reconstruction such as choice of graft, graft fixation method of patella/femur and initial tension. We describe short term clinical results of MPFL reconstruction by using soft suture anchor and adjustable cortical fixation system. METHODS: Twenty-four patients who underwent isolated MPFL reconstruction by using soft suture anchor and adjustable cortical fixation system were included in this study. All patients were followed up for at least 2 years, and pre-operative and 2 years post-operative Kujala score, IKDC score and Knee Injury and Osteoarthritis Outcome Score were used to assess clinical outcome. Radiographic evaluation included the Q angle, congruence angle and patellar tilt angle. Pre- and post-operative changes were evaluated by Mann–Whitney U test. RESULTS: There were no complications including re-dislocation, patella fracture, infection, and joint contracture. The apprehension test was positive in 4.2% post-operatively. A statistically significant improvement in clinical scores and radiographic evaluation were evident after surgery. CONCLUSIONS: Isolated MPFL Reconstruction using soft suture anchor and adjustable cortical fixation system led good restoration of patellar stability and significant improvement of knee function in short-term results. This surgical technique can reduce complications such as patella fractures, and can be done safely. CLINICAL RELEVANCE: This technique may be a treatment option with little associated complications in the treatment for patellar instability. LEVEL OF EVIDENCE: Case series, Level IV.